Data visualization on top highest grossing movie in Hollywood using Python / Mohamad Islahuddin Abdul Malek - Abdul Malek, Mohamad Islahuddin (2022)
Data visualization on movies with the top highest quotes in Hollywood is a visualization technique based on secondary data about movie quotes in Hollywood. The goal of this secondary data visualization is to study current film flow patterns because recording companies can use descriptive analysis to make judgments about film production in terms of quality, appeal and genre that can appeal to audiences. The second problem is that the rankings shown from the site still use the current manual which does not have the latest information or the latest rankings from the latest movies. Therefore, data visualization on Hollywood movies with the highest citations using python is proposed to address the problem issue. This prototype will help users analyse or find Hollywood movies with easy positioning using this method. In addition, users can also view multi -pattern graphs by using this prototype by year or type of data to be studied for example by year or type of film genre. In addition, this prototype methodology consists of three phases, project framework, system development and evaluation phase. Then, a consumer acceptance test was conducted with 30 respondents to determine the effectiveness in film collection in the Hollywood ranking count. Visualizing the top highest grossing movies in Hollywood using Python is positively accepted by most of the public to make the effectiveness of grossing movies in Hollywood ranking count more effective and efficient. Thus, by using this system, user can check the grossing movies in Hollywood ranking count more easily with Python without involving less accurate data.